ISLAM DAN KEBUDAYAAN: WAYANG SEBAGAI MEDIA PENDIDIKAN ISLAM DI NUSANTARA - Marsaid, M (IAIN Tulungagung, 2016)
This article tries to show the values of monotheism in the process of Islamisation of the local culture through local culture, like a puppet. Puppetis a product of culture that existed long before Islam arrived in Indonesia,especially Java. Sunan Kalijaga made the puppet as a means and media propagation of Islam through art and culture. The material and appearance of the puppet assimilated with the doctrine of Islam through languages more Islamic and instilling monotheism. By reviewing the literature, this paperdescribes the puppet discourse developed in the perspective of Sunan Kalijaga Islamic education. That the puppet that has become the cultural heritage of this archipelago since the early period of Islamisation has offered material and doctrines of Islam through javanes languages with relevant and easily understood by the surrounding community.Keywords: Wayang, Islamic tradition, Sunan Kalijaga